Effects of salinity, organic acids and alkalinity on the growth of calcite spherulites: Implications for evaporitic lacustrine sedimentation. (1st February 2021) - Mercedes‐Martín, Ramon; Rao, Ashit; Rogerson, Mike; Sánchez‐Román, Mónica
Abstract: Lacustrine non‐skeletal carbonates exhibit a diversity of petrographies due to interactions between physico‐chemical and biologically influenced mechanisms. Despite the suggestion that evaporative concentration was involved in the formation of spherulite and shrubby‐bearing carbonate successions in the Pre‐Salt Cretaceous alkaline lakes of the South Atlantic, no consensus exists about the water chemistries promoting these exotic mineral textures. In this work, an experimental approach was developed to evaluate how changes in salinity (NaCl) and biopolymer concentrations (alginic acid) impact calcite growth dynamics from saline and alkaline synthetic solutions. Hydrochemical and petrographical data from selected modern saline/alkaline environments were compared with experimental datasets to further estimate how the underlying (bio)chemical conditions and lake locations probably converge to allow the formation of calcite spherulite grains in evaporitic settings. Spherulitic calcite from Recent saline lakes and experiments arise from waters with moderate to high [Calcium]/[Alkalinity] ratios ([Ca]/[Alk]) rather than in calcium‐depleted and alkaline‐rich environments which tend to produce single‐crystal calcites during abiotic water mixing or lake evaporation. This observation is consistent with the assembly of polycrystalline textures being a kinetically controlled feature, forced by remarkably high rates of nucleation. Also, the data analysed do not support a causative relationship between evaporite‐driven salinity fluctuations and the preferential formation of spherulites, shrubs or their intermediate textures. Ubiquitous in saline lakes, organic substances can lower the kinetic thresholds for spherulitic calcite aggregation while microbial photosynthesis can also raise pH, altogether enhancing calcite supersaturation and promoting spherulite formation in waters with moderate‐high [Ca]/[Alk] ratios and high salinities. Localised observations of abiotic spherulites in Recent soda lakes can occur in restricted mixing zones where [Ca]/[Alk] ratios are enhanced. This work highlights the roles of concentration regimes associated with biopolymers and microbial metabolism against the background salinity fluctuations in determining the morphological and textural transitions in lacustrine carbonate minerals. Abstract : We compared hydrochemical and petrographical data from selected modern saline/alkaline carbonate environments and experimental datasets to evaluate the roles that salinity, biopolymer concentrations and microbial metabolism have in the formation of calcite spherulite grains in lacustrine evaporitic settings.